2008
DOI: 10.1017/s0266462308080446
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the quality of clinical practice guidelines on established ischemic stroke

Abstract: The overall quality of the CPGs published for ischemic stroke management did not have minimum methodological quality. Quality improvement has been observed in more recent CPGs and may be due to the publication of new tools such as the AGREE or CPP instruments, as well as international initiatives for CPG improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
2
8
1
1
Order By: Relevance
“…Results of the AGREE II analysis revealed that there was significant variability in the quality of the CPGs under review, a similar result to that found in a 2007 study, which also examined the quality of stroke CPGs . Although the domain areas of scope and purpose, clarity and presentation, and editorial independence scored in the high range, lower domain scores were in the areas of stakeholder involvement, rigour of development and applicability as Navarro, Puerto et al . (2008) also found.…”
Section: Discussionsupporting
confidence: 74%
“…Results of the AGREE II analysis revealed that there was significant variability in the quality of the CPGs under review, a similar result to that found in a 2007 study, which also examined the quality of stroke CPGs . Although the domain areas of scope and purpose, clarity and presentation, and editorial independence scored in the high range, lower domain scores were in the areas of stakeholder involvement, rigour of development and applicability as Navarro, Puerto et al . (2008) also found.…”
Section: Discussionsupporting
confidence: 74%
“…Only two were evaluated as not recommended 41 44. This contrasts with the evaluations of other CPG in other areas where the quality is clearly lower 56 57. Contrary to what might have been expected, in terms of improvement over time, little improvement was detected after the implementation of the AGREE instrument published in 2003.…”
Section: Discussioncontrasting
confidence: 74%
“…Furthermore, there is room for improvement in the area of editorial independence, as only 14 guidelines (63.6%) included a conflict-of-interest statement, and only two provided information about the funding sources. Despite the generally accepted policy of conflict of interest statements in medical journals, this has not yet been widely adopted in CPGs 56. Our results stress the need for improvement in the quality of guidelines in the field of perioperative care, particularly when these decision-making tools claim to be an essential link in the knowledge-translation process.…”
Section: Discussionmentioning
confidence: 70%
“…These organizations include the National Institute for Health and Clinical Excellence (NICE) [46,50,53,54], the Scottish Intercollegiate Guidelines Network (SIGN) [53,55], the New Zealand Guidelines Group [43], the Royal College of Physicians of London [55], and the Canadian Task Force on Prevention Health Care group [55]. The American College of Chest Physicians (ACCP) evidence-based CPGs on anti-thrombotic therapy and prevention of thrombosis, rigorously addressed several of the aforementioned caveats encountered in many CPGs [56-59].…”
Section: Discussionmentioning
confidence: 99%